An Unconventional Flavivirus and Other RNA Viruses in the Sea Cucumber (Holothuroidea; Echinodermata) Virome - Ian Hewson; Mitchell R. Johnson; Ian R. Tibbetts (Viruses, 2020)
Sea cucumbers (Holothuroidea; Echinodermata) are ecologically significant constituents of benthic marine habitats. We surveilled RNA viruses inhabiting eight species (representing four families) of holothurian collected from four geographically distinct locations by viral metagenomics, including a single specimen of Apostichopus californicus affected by a hitherto undocumented wasting disease. The RNA virome comprised genome fragments of both single-stranded positive sense and double stranded RNA viruses, including those assigned to the Picornavirales, Ghabrivirales, and Amarillovirales. We discovered an unconventional flavivirus genome fragment which was most similar to a shark virus. Ghabivirales-like genome fragments were most similar to fungal totiviruses in both genome architecture and homology and had likely infected mycobiome constituents. Picornavirales, which are commonly retrieved in host-associated viral metagenomes, were similar to invertebrate transcriptome-derived picorna-like viruses. The greatest number of viral genome fragments was recovered from the wasting A. californicus library compared to the asymptomatic A. californicus library. However, reads from the asymptomatic library recruited to nearly all recovered wasting genome fragments, suggesting that they were present but not well represented in the grossly normal specimen. These results expand the known host range of flaviviruses and suggest that fungi and their viruses may play a role in holothurian ecology.